Commentary on the Financial Stability Forum's report of the Working Group on Capital Flows - Cornford, Andrew (UN New YorkUS)
Focuses mainly on changes in recipient countries in practices with regard to the monitoring and management of financial risks, rather than on changes in the main sources of international lending and investment.